2018
DOI: 10.3390/nu10030381
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Water-Soluble Forms of Choline in Human Milk from Lactating Women in Canada and Cambodia

Abstract: Choline has critical roles during periods of rapid growth and development, such as infancy. In human milk, choline is mostly present in water-soluble forms (free choline, phosphocholine, and glycerophosphocholine). It is thought that milk choline concentration is influenced by maternal choline intake, and the richest food sources for choline are of animal origin. Scarce information exists on milk choline from countries differing in animal-source food availability. In this secondary analysis of samples from pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
5
15
2
Order By: Relevance
“…In regards to the variability of water-soluble forms of choline concentration in expressed human milk, we observed diurnal changes in milk FC and GPC concentrations, but not in PhosC and total water-soluble choline forms. The total concentration of water-soluble forms of choline in expressed human milk we found was similar to the concentrations previously reported by our team for Canadian lactating women [24,32] and by Fischer et al for US women [11]. Because no substantial diurnal changes were observed and the total concentration of water-soluble forms of choline in human milk seems stable, we conclude that the time point of milk sample collection in studies on water-soluble forms of choline may not influence the study outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In regards to the variability of water-soluble forms of choline concentration in expressed human milk, we observed diurnal changes in milk FC and GPC concentrations, but not in PhosC and total water-soluble choline forms. The total concentration of water-soluble forms of choline in expressed human milk we found was similar to the concentrations previously reported by our team for Canadian lactating women [24,32] and by Fischer et al for US women [11]. Because no substantial diurnal changes were observed and the total concentration of water-soluble forms of choline in human milk seems stable, we conclude that the time point of milk sample collection in studies on water-soluble forms of choline may not influence the study outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, for this preliminary study, we were mainly focusing on the comparison of choline concentrations between before and after pasteurization. We acknowledge that the long-term storage at −80 • C may have affected the milk concentrations of the water-soluble forms of choline; however, the total water-soluble choline concentration in the pre-pasteurized samples was similar to that of the fresh milk samples in the stability study (1241 µmol/L versus 1231 µmol/L, respectively), as well as compared to those reported in the literature [11,24,32]. This seems to reflect that the total water-soluble choline concentration was not affected by the long-term storage at −80 • C and that our findings may contribute to the literature of how human milk is altered by pasteurization.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, free choline represents only a small fraction of the total choline in human milk; thus, this difference may not be of biological relevance. Recently, we published the first report on concentrations of the water-soluble forms of choline in mature milk samples from lactating women in Canada and Cambodia [ 137 ]. Our results indicated that the concentrations did not differ between Canadian and Cambodian women.…”
Section: Choline Content In Dietary Food Sourcesmentioning
confidence: 99%
“…Choline has been recognized as an essential nutrient [ 38 ]. Choline concentration in human mature milk was shown to be stable regardless of maternal age and intake [ 39 ]. However, limited data are available on choline concentration in bovine milk related to β-casein variants.…”
Section: Discussionmentioning
confidence: 99%